THE ANALYSIS OF LEAD CONTENT (Pb) IN CRABS (portunus pelagicus) IN THE COASTAL WATERS OF MA’RANG SUB-DISTRICT OF PANGKEP DISTRICT - sulfiani ani Hasan (Sekolah Tinggi Pariwisata Mataram, 2020)
The waters of Ma'rang Subdistrict, Pangkep Regency, have the potential to be contaminated with heavy metal lead (Pb), which is used as a place for fishing and marine products. The use of gasoline by boats as a means of transportation for looking for small crabs (Portunus Pelagicus), farming seaweed, or other marine products are thought to cause heavy metal lead (Pb) in these waters. The purpose of this study was to determine the contamination of the heavy metal lead (Pb) in the crab (Portunus Pelagicus) and to determine the content of the heavy metal lead (Pb) in the crab (Portunus Pelagicus). The method of this research was the Atomic Absorption Spectrophotometer (AAS) by analyzing the lead (Pb) content of the crab (Portunus Pelagicus) obtained in the waters around the jetty in the coastal area of ​​Ma'rang District, Pangkep Regency. The results showed that the lead content (Pb) in the crab (Portunus Pelagicus) in the coastal waters of Ma'rang District, Pangkep Regency, for samples from Bawa Salo Pier, the lead content was 0.0059 μg/g, the sample from Pungkalawaki Pier obtained a lead range of 0.0796 μg/g, samples from Dusunge Wharf obtained lead levels of 0.0236 μg / g, samples from Jennae Wharf obtained lead levels of 0.0064 μg/g, and samples from Kessi Wharf obtained lead levels reaching 0.0944 μg/g. Based on BPOM Regulation Number 5 of 2018, the lead content obtained from crabs (Portunus Pelagicus) is still below the threshold of 0.20 μg/g